Heritage environment and cultural legacy system in Lý Sơn Island District (Quảng Ngãi Province – Vietnam) - Hau, Nguyen Thi (Edelweiss Applied Science and Technology, 2025)
Ly Son, an island district of Quang Ngai province, is strategically located in the South Central Coast of Vietnam. This study examines the interrelationship between the heritage environment, the cultural heritage system, and the local community of the island, with an emphasis on historical relics and rituals. It explores the dynamic interaction between these elements. Approaching from the archaeology of religion and ritual and community archaeology, the study clarifies the origin and function of religious relics, as well as the close relationship between the community and cultural heritage. The findings indicate that Ly Son’s traditional livelihood revolves around sea exploitation. The cultural heritage system centers on the worship of sea gods, with the community organizing rituals and festivals in their honor. Most notably, these are the relics and festivals commemorating the people of Ly Son island who sacrificed their lives at sea. The research results emphasize that currently, maintaining and developing the marine economy is the most important factor in preserving the cultural heritage on Ly Son Island. Concurrently, it provides valuable recommendations for the government and local authorities in building policies to support the sustainable development of Ly Son while protecting the unique cultural heritage system of this island.